Pengaruh Pembiasaan Membaca Nadhom Aqidatul Awam Terhadap Akhlak Peserta Didik Smpit Bahrul Ulum Gili-Gili Sukakarya Kabupaten Bekasi - Nurul, Dinda Azkiya; Abdurrohim, Abdurrohim; Mustofa, Taufik (Jurnal Ilmiah Wahana Pendidikan, 2024)
Morals in religious education are something that must be given to students and occupy a very important position. One of the most important goals is the overall development of morals, including a student's relationship with God and with himself and also with the community in his environment. In this case, providing moral education to students is very important and should not be neglected in daily learning implemented in schools. Habituation is something that is done repeatedly so that someone gets used to the correct behavior, behavior or way of thinking. In this case, SMPIT Bahrul Ulum Gili-Gili Sukakarya Bekasi Regency has a habit, one of which is the activity of reading nadhom aqidatul lay in the formation of students' morals. The method used in this research is a quantitative approach with correlational methods. From the results of the calculations that have been carried out, it is known that 12.5% ​​are in the low category, 65.62% are in the medium category and 21.87% are in the high category, so it can be concluded that the average moral of students in the habit of reading nadhom aqidatul lay at SMPIT Bahrul Ulum Gili-Gili Sukakarya, Bekasi Regency is in the medium category.